1973
DOI: 10.1017/s0079497x0001166x
|View full text |Cite
|
Sign up to set email alerts
|

A New Survey of Grime's Graves—First Report

Abstract: SummaryNo accurate survey of a flint mine exists. It is planned to carry out such a survey at Grime's Graves over a period of several years. Its purpose is to study the growth of the flint-mine complex, the evaluation of mining techniques and ancillary industries, and trade relations; and to discover settlement sites related to the industrial complex. Preliminary field work was carried out in the summer of 1972. This included geophysical and chemical surveys, ground surveys, and aerial photography. Excavations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The application of phosphate analysis in archaeology was first developed in Europe in the 1930s, where pioneering efforts by Arrhenius (1931) and Lorch (1940) were followed by work of numerous scholars, including Dauncey (1952), Sieveking et al (1973), andProvan (1973). Their results indicated that areas of ancient occupation showed elevated concentrations of phosphate.…”
Section: Methodological History Of Phosphate Analysis In Archaeologymentioning
confidence: 99%
See 1 more Smart Citation
“…The application of phosphate analysis in archaeology was first developed in Europe in the 1930s, where pioneering efforts by Arrhenius (1931) and Lorch (1940) were followed by work of numerous scholars, including Dauncey (1952), Sieveking et al (1973), andProvan (1973). Their results indicated that areas of ancient occupation showed elevated concentrations of phosphate.…”
Section: Methodological History Of Phosphate Analysis In Archaeologymentioning
confidence: 99%
“…The most common application of soil phosphate analysis in archaeology is for pre-excavation prospection to locate or delimit archaeological sites (e.g., Ball and Kelsay, 1992;Dauncey, 1952;Eidt, 1984;Hammond, 1983;Provan, 1973;Sieveking et al, 1973). Soil chemical data provide important clues about activities within a given area when it has been difficult to judge from artifact data alone (e.g., Ball and Kelsay, 1992;Cavanagh et al, 1988;Coultas et al, 1993;Dunning, 1993;Lippi, 1988).…”
Section: Methodological History Of Phosphate Analysis In Archaeologymentioning
confidence: 99%
“…First, soil phosphates are analyzed in preexcavation prospecting to locate or delimit archaeological sites before excavation. This has been the most common use of phosphate analysis in archaeology (e.g., Dauncey, 1952;Provan, 1973;Sieveking et al, 1973;Hassan, 1981;Hammond, 1983;Eidt, 1984;Ball and Kelsay, 1992). Second, phosphate analysis is used as a tool in landscape archaeology to examine past agricultural practice (Coultas et al, 1993;Lippi, 1988;Dunning, 1993;Dunning et al, 1997Dunning et al, , 1998.…”
Section: Phosphorus Measurement and Archaeologymentioning
confidence: 99%
“…Previous excavations (Clarke, 1915;Greenwell, 1871) (R, 1961, v 3, p 41;1963, v 5, p 106;1969, v 11, p 285;Burleigh, 1975). Excavation of a shaft at Grime's Graves in [1971][1972] yielded 7 more samples of antler and charcoal which provided dates in good general agreement with those for the material from the earlier excavations (R, 1976, v 18, p 32;Mercer, 1976;Sieveking et al, 1973).…”
mentioning
confidence: 95%